God on Earth: Emperor Domitian. The re-invention of Rome at the end of the 1st century AD - de Sousa Cotrim, Irlan (Romanitas - Revista de Estudos Grecolatinos, 2023)
Review of: COMINESI, A. R.; HAAN, N. de; MOORMANN, E.; STOCKS, C. (ed). God on Earth: Emperor Domitian. The re-invention of Rome at the end of the 1st century AD. Leiden: Sidestone Press, 2021.
Keywords: Domitian; Archaeology; Principate